DETERMINANT OF FIRM VALUE WITH FIRM SIZE AS A MODERATING VARIABLE - Amelia, Wyne; Yanti , Yanti (International Journal of Application on Economics and Business, 2025)
The capital market, commonly referred to as the stock exchange, is the marketplace where the seller and the buyer, in this example a firm acting as the seller and an investor as the buyer, come together to trade different long-term financial instruments. This study is implemented with aims to examine the effect of profitability assessed by roa on company value by pbv with firm size as a moderating variable in property and real estate companies listed on BEI during the 2020 – 2022 period were used as study objects. A quantitative method is used to this study with 31 companies as study objects, measured by purposive sampling techniques. This study uses a panel data regression model with Fixed Effect Model (FEM) approach using Eviews version 12 program. The result of this research shows that profitability has no influence on company value. Moreover, the result of this study also shows that company size is able to moderate (weaken) the influence of profitability on company value.